A practical approach for scaling up the alternative strategy for the elimination of lymphatic filariasis in Loa loa endemic countries - developing an action plan - Louise A. Kelly-Hope; Michelle C. Stanton; Honorat G. M. Zouré; Boniface E. Kinvi; Alexei Mikhailov; Afework Tekle; Jonathan D. King (BMC, 2017)
Abstract Background Lymphatic filariasis (LF) is a vector-borne parasitic disease that is being targeted for elimination through mass drug administration (MDA). The co-distribution of Loa loa in Central Africa poses a significant barrier to the expansion of the MDA due to risk of severe adverse events (SAEs) associated with the drug ivermectin that is routinely used. National LF programmes are yet to significantly scale up in co-endemic areas and need a practical approach to make preliminary decisions based on the mapping status and potential treatment strategies. Methods We reviewed relevant data available to WHO and in the literature for LF-L. loa endemic countries to develop a simple method to support the scale-up of MDA to eliminate LF. Results A basic model for national LF programmes to work from at the administrative or implementation unit (IU) level has been developed for LF - L. loa co-endemic countries. The model includes five practical steps, which comprise the development of a national filarial database and a simple classification system to help determine the mapping status and most appropriate treatment strategy. Steps are colour-coded and linked to a general decision tree, which is also presented. Conclusions This IU-level model is simple to follow and will help LF elimination programmes develop an action plan and scale up the implementation of alternative treatment strategies in L. loa co-endemic areas. The model could be further developed to incorporate the additional complexity of IUs where an intervention is required to eliminate onchocerciasis, particularly in hypo-endemic areas where ivermectin has not been used.